The effect of IL 6 174G>C gene polymorphism on gastrointestinal cancer: a systematic review and meta analysis - Darvishi, Niloofar; Salari, Nader; Bokaee, Shadi; Shohaimi, Shamarina; Mohammadi, Masoud (Springer (India) Private, 2023)
IL-6 gene polymorphisms can play a role in the development or control of cancer by afecting cytokines. Gastrointestinal cancer is one of the most common types of cancer worldwide. The aim of this study was to investigate the efect of polymorphism of the IL-6 174G>C gene on gastrointestinal cancers based on a systematic review and meta-analysis, including gastric, colorectal, and esophageal cancer. In this study, a systematic and meta-analytical review of the study data on the efect of polymorphism of IL-6 174G>C gene on gastrointestinal cancer (gastric, colorectal, and esophageal cancer) in Scopus, EMBASE, Web of Science, PubMed, and Science Direct Databases was extracted without any time limit until April 2020. In order to perform the analysis of eligible studies, the model of random efects was used and the heterogeneity of studies was investigated with I 2 index. Data analysis was performed with Comprehensive Meta-Analysis software (Version 2). The total number of surveyed studies in patients with colorectal cancer was 22 studies. Based on the results of meta-analysis, the odds ratio of GG genotype in patients with colorectal cancer was 0.88. The odds ratio of GC genotype obtained in patients with colorectal cancer was 0.88 and the odds ratio of CC genotype in patients with colorectal cancer was 0.92. The total number of surveyed studies in patients with gastric cancer was 12. Based on the meta-analysis results, the odds ratio of GG genotype in patients with gastric cancer was 0.74, the odds ratio of GC genotype in patients with gastric cancer was 1.27, and the odds ratio of CC genotype in patients with gastric cancer was 0.78. The total number of surveyed studies in esophageal cancer patients was 3 studies. Based on the results of meta-analysis, the odds ratio of GG genotype in patients with esophageal cancer was 0.57, the odds ratio of GC genotype in patients with esophageal cancer was 0.44, and the odds ratio of chance of CC genotype in patients with esophageal cancer was 0.99. In general, diferent genotypes of polymorphism of the IL-6 174G>C gene reduce the risk of gastric, colorectal, and esophageal cancer. However, the GC genotype of this gene was associated with a 27% increased risk of gastric cancer.